Study of the Mechanical and Energetic Properties of Pellets Produce from Agricultural Biomass of Quinoa, Beans, Oat, Cattail and Wheat - Alarcon M. (2017)
This work was supported by a Grant of Concytec, L´oreal and UNESCO “For Women in Science” Peru 2013, Project: Processing of agricultural wastes to fuel that can be used in kitchens of Andean rural areas with less environmental domestic impact.